PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KONSEP SISTEM PERNAPASAN MANUSIA PADA KELAS XI SMA PGRI 1 AMBON - Friescilya Beatrix Latuperissa; Dominggus Rumahlatu (Program Studi Pendidikan Biologi FKIP Unpatti, 2018)
Background: Education is defined as a process using certain models so that one can obtain knowledge, understanding, and ways of behaving according to needs. In this study aims to determine the effect of applying the snowball throwing learning model in improving learning outcomes on the concept of the human respiratory system in class XI SMA PGRI 1 Ambon Method: This study was conducted from February 14 to March 14, 2018 in class XI SMA PGRI 1 Ambon. Results: Through cooperative design shows that there is an increase in learning outcomes after using the snowball throwing model. Conclusion: The application of the Snowball Throwing type cooperative learning model can improve the learning outcomes of the concept of human respiratory system in class XI IPA2 students of SMA PGRI 1 Ambon showing the level of success of students seen from cognitive, affective, psychomotor and final grades.